Green Synthesis and Bioactivity Screening of Zinc Oxide Nanoparticles: In Vitro Investigation of Wound Healing, Antioxidant, and Antibacterial Properties - Wankhede, Sujata Vinod; Muskan, Mahalaxmi; Gupta, Geetika; Roychowdhury, Victor; Shekhar, S. Raja; Kumar, Anil; Prasad, Shilpi; Patel, Kinjal P.; Singh, Gagandeep (Journal of Neonatal Surgery, 2025)
Background: Zinc oxide nanoparticles (ZnO NPs) are increasingly explored in biomedicine due to their multifunctional properties. However, traditional synthesis methods involve toxic reagents and high energy input. Green synthesis using plant extracts offers an eco-friendly alternative, with phytochemicals acting as natural reducing and stabilizing agents. This study investigates the green synthesis of ZnO NPs and evaluates their antioxidant, antibacterial, and wound healing activities. Methods: ZnO NPs were synthesized using aqueous plant extract, followed by characterization via UV-Vis spectroscopy (peak at 375 nm), FTIR (evidence of phenolic and hydroxyl capping), XRD (hexagonal wurtzite structure; average size 24 nm), SEM (spherical morphology), and EDX (elemental confirmation of Zn and O). Antioxidant activity was assessed via DPPH, ABTS, and FRAP assays, with IC₅₀ values compared to ascorbic acid. Antibacterial activity was tested using the agar well diffusion method against E. coli and S. aureus. In vitro wound healing potential was evaluated using a scratch assay on HaCaT cells over 48 hours. Data were statistically analyzed (ANOVA, p < 0.05). Results: The ZnO NPs demonstrated potent antioxidant activity with an IC₅₀ of 49.2 µg/mL (DPPH), comparable to the standard. Antibacterial activity showed zones of inhibition of 18.2 ± 1.1 mm (S. aureus) and 15.6 ± 0.9 mm (E. coli) at 100 µg/mL. In wound healing assays, ZnO NPs achieved 82.4% closure at 48 h, significantly higher than untreated controls. Characterization confirmed nanoscale size, purity, and plant-derived capping. Conclusion: Green-synthesized ZnO NPs exhibit strong antioxidant, antibacterial, and wound healing properties, indicating their potential in biomedical applications such as wound dressings and antimicrobial formulations. Further in vivo studies and formulation development are recommended.